2020
DOI: 10.1111/sdi.12907
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre analysis of the outcome of arteriovenous fistula in maintenance haemodialysis

Abstract: Introduction: Arteriovenous fistulas (AVF) are the preferred choice for vascular access in hemodialysis. We aim to identify factors that may contribute to AVF failure. Methods: Data regarding AVF survival were collected from 441 patients. All AVFs were either radial or brachial, of the end‐to‐side variety. Parameters studied were age, gender, diabetes mellitus, hypertension prior to end‐stage kidney disease (ESKD), site of fistula, blood flow rate, venous pressure, dialysis vintage and frequency, needle gauge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…MHD access is the lifeline of treatment for patients with endstage renal disease, but it is easy to have narrow and blocked vascular access during treatment, resulting in significantly reduced hemodialysis flow, seriously affecting the final therapeutic effect and prognosis of patients [18][19][20]. Balloon dilatation of AVFs, as the treatment of choice for MHD, is widely used in clinical practice because of its characteristics of less susceptibility to infection and a long duration of patency [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…MHD access is the lifeline of treatment for patients with endstage renal disease, but it is easy to have narrow and blocked vascular access during treatment, resulting in significantly reduced hemodialysis flow, seriously affecting the final therapeutic effect and prognosis of patients [18][19][20]. Balloon dilatation of AVFs, as the treatment of choice for MHD, is widely used in clinical practice because of its characteristics of less susceptibility to infection and a long duration of patency [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some observational studies continue to report AVF maturation rates in older adults that are similar to the profile of AVF development in younger counterparts [ 34 ]. Other studies suggested no significant difference in AVF maturation and survival rates by age, sex, and presence of diabetes mellitus [ 35 ]. Clinical trials that analyze access-related outcomes following AVF vs. AVG creation in a highly pertinent context, i.e., older adults with comorbidities linked with AVF failure, would meet the goal of providing information for patient-tailored clinical decision.…”
Section: Age-dependent Biological Factors Independently Affect Vascul...mentioning
confidence: 99%
“…Trong đó: n: Cỡ mẫu nghiên cứu cần có; P: Tỷ lệ mẫu ước tính; α: Mức ý nghĩa thống kê thường là 0.05; d: Khoảng sai lệch mong muốn giữa tham số mẫu và tham số quần thể; Z(1-α/2): Giá trị Z thu được tương ứng với mức ý nghĩa thống kê mong muốn. Với tiêu chí đánh giá hiệu quả phẫu thuật qua biến chứng (nếu có), dựa vào một số nghiên cứu tương tự như Nguyễn T.Quyên(2017) [2], Sa M.Dương (2019) [3], Nguyễn Đ.Nhân(2023) [4] biến chứng cầu nối trong khoảng 5-20%, chúng tôi chọn p = 0,1, d = 0,1. Thế vào công thức, được n = 34,57.…”
Section: Cỡ Mẫu Chọn Mẫuunclassified
“…Tuy nhiên, có thể gặp kích thước mạch trên siêu âm và phẫu thuật khác nhau. Một phân tích đa trung tâm cho thấy trước phẫu thuật đường kính động mạch >2mm, tĩnh mạch >2,5mm, miệng nối phẫu thuật > 04mm tỷ lệ thành công cao hơn hẳn [4].…”
Section: đáNh Giá Mạch Máu Bằng Siêu âM Mappingunclassified